A critical review of advanced oxidation processes for emerging trace organic contaminant degradation: Mechanisms, factors, degradation products, and effluent toxicity. (April 2021) - Tufail, Arbab; Price, William E.; Mohseni, Madjid; Pramanik, Biplob K.; Hai, Faisal I.
Highlights: Mechanisms/factors governing TrOC degradation by AOP are critically reviewed. Factors include TrOC molecular structure, water chemistry and oxidant dosage. Organic/inorganic ions coexisting with TrOC may enhance or retard TrOC degradation. Interfering ions form radicals that oxidise TrOC and enhance TrOC degradation. Type and concentration of TrOC and AOP treatment affect by-products pathway. Abstract: The persistent nature and low biodegradability of a large number of trace organic contaminants (TrOCs) reduce effectiveness of their removal by conventional wastewater treatments. In this context, advanced oxidation processes (AOPs), such as photolysis, photocatalysis, ozonation, Fenton process, anodic oxidation, sonolysis and wet air oxidation, have been studied extensively for the effective degradation of the wide range of TrOCs. All AOPs produce reactive oxygen species (HO2 ●, O2 ●− ), especially hydroxyl radicals that unselectively attack contaminants and oxidise them. Factors affecting the degradation rates of TrOCs by different AOPs include the concentration and nature of the TrOCs, bulk wastewater characteristics, dose of chemicals or catalysts used, and other reaction parameters. This review critically analyses the overview of already established AOPs, the effect of the structure of TrOCs based on different functional groups such as electron donating groups (EDGs) and electron withdrawing groups (EWGs) on their degradation by each AOP. The overall degradation rates based on data collected from a comprehensive literature review show that ozonation achieves effective degradation for a broad range of TrOCs, but it can lead to the production of toxic degradation by-products. By comparison, photocatalysis shows moderate to high degradation rate for TrOCs. Photolysis and Fenton processes show TrOC-specific suitability. This review also demonstrates that optimum doses of chemicals/catalysts are required for each AOP. This is because excessive concentrations of catalysts or other chemicals ( e.g ., H2 O2 : iron dose in Fenton process) may result in low TrOC degradation. Degradation of individual TrOCs can result in a number of degradation by-product that varies in nature. Different AOP has different reaction mechanisms that also affect the number and nature of by-product formation during TrOC degradation.